(untitled) (LACCEI, 2024)
Cylindrical nanoparticles immersed in an absorbing environment were studied by evaluating the solutions of Maxwell’s equations in a cylindrical symmetry with dispersive materials interacting with electromagnetic radiation. Analytical solutions are developed for the efficiencies, dispersion (Qs), for different complex refractive indices of materials found in the literature. The scattering is derived from the near field solutions on the surface of the studied nanoparticle. The results show that, although the absorbing medium significantly reduces the scattering efficiency, we also studied the intensity of the stray electromagnetic field at different wavelengths and with different sizes of nanoantennas, finely studying the phase profile in terms of the scattering angle